Manganese- and rhenium-catalyzed C–H enaminylation: expedient access to novel indole–purine hybrids with anti-tumor bioactivities. Issue 22 (26th October 2020) - Xu, Zhongnan; Wang, Yuqing; Zheng, Yucheng; Huang, Zhixing; Ackermann, Lutz; Ruan, Zhixiong
Abstract : The C–H enaminylation of novel 6-(1 H -indol-1-yl)-purines with ketenimines was accomplished by means of aqueous manganese and rhenium catalysis, which sets the stage for the facile synthesis of indole–purine hybrids with anti-tumor bioactivities. Abstract : The C–H enaminylation of novel 6-(1 H -indol-1-yl)-purines with ketenimines was accomplished by means of eco-friendly aqueous manganese catalysis as well as rhenium catalysis with low catalyst loading. The versatile C–H enaminylation features unparalleled broad substrate scope with good yields, and high levels of chemo-, site- and regio-selectivity. The well-defined organometallic C–H functionalization sets the stage for the facile synthesis of indole–purine hybrids with anti-tumor bioactivities.